A prolegomenon to the study of pottery stamps from Mes Aynak. Issue 2 (October 2018) - Lerner, Judith A.
Abstract : That Afghanistan has been a cultural crossroads is no better demonstrated than by its glyptic art. The designs and styles of the seals used to sign, authenticate and secure documents and packages reflect the artistic and religious traditions of the Hellenistic, Iranian, and Indian worlds. A particular category of seal design is, to my knowledge, known only from impressions on the exterior of clay vessels; they occur at a number of sites in Afghanistan. Their designs differ in style and imagery from the glyptic art of the regions and cultures that produced seals used for authentication purposes and thus suggest that they were carved specifically to mark or decorate ceramics. Recently, a number of potsherds with such seal impressions have been salvaged at the major Buddhist site of Mes Aynak, 40 km southeast of Kabul. Some share motifs with stamped pottery from other sites in Afghanistan, but others are unique. This article is a preliminary exploration of the subject matter and style(s) of the Mes Aynak pottery stamps.